SUPPLIER SELECTION FOR IMPROVING SUPPLY CHAIN PERFORMANCE - Novianti Adi Rohmanna; Imam Santoso; Zuliyan Agus Nur Muchlis Majid (AGROINTEK, 2022)
Supplier selection played a role in developing industry performance. It was one of the critical issues in supply chain management. This study illustrated applying a decision-making procedure for supplier selection on KUD Dau Batu by ANP and fuzzy TOPSIS. Four suppliers (Princi, Gading Kulon, Petung Sewu, and Kucur) thought qualified for procuring milk. The first step determined the weight of criteria and sub-criteria that impacted strategic supplier selection by ANP. This approach in a KUD Dau Batu showed that cost was the top priority. The next step was to defuzzification of criteria and ranking the four suppliers by fuzzy TOPSIS. The supplier from Kucur was the best milk supplier compared to other supplier.